A good year for the roses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Flowers love people, but no love is lost in the Dutch flower auction in Aalsmeer. ACP and other Southern countries command a fifth of this market, where you never cut corners, nor quality. Is it curtains for coffee, cotton, tea and cocoa?...